2007
DOI: 10.1037/0278-6133.26.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the impact of episodic and chronic stressors on hypothalamic-pituitary-adrenocortical axis regulation in young women.

Abstract: The impact of episodic stress is accentuated in the midst of chronic interpersonal stress and diminished in its absence. Simultaneous exposure to episodic and chronic stress may create wear and tear on the body, whereas exposure to episodic stress in the context of a supportive environment may toughen the body, protecting it against subsequent stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 49 publications
0
61
0
Order By: Relevance
“…Marin and colleagues conducted a cross-sectional analysis of 104 young women in 2007 [87]. This study also found a significant relationship between CRP levels and acute as well as chronic interpersonal stress.…”
Section: Interpersonal Stressmentioning
confidence: 84%
See 1 more Smart Citation
“…Marin and colleagues conducted a cross-sectional analysis of 104 young women in 2007 [87]. This study also found a significant relationship between CRP levels and acute as well as chronic interpersonal stress.…”
Section: Interpersonal Stressmentioning
confidence: 84%
“…Three studies examined the relationship between interpersonal stress and CRP [81,86,87]. In a 2009, Fuligni and colleagues [86] asked 69 high school seniors to maintain a standardized diary of interpersonal stress for 2 weeks.…”
Section: Interpersonal Stressmentioning
confidence: 98%
“…Although other studies have found a positive relation between stressful experiences and cortisol activity (Bevans et al, 2008;Marin, Martin, Blackwell, Stetler, & Miller, 2007;Rao, Hammen, Ortiz, Chen, & Poland, 2008), the time between exposure to adversity and cortisol assessment in many of these studies was much shorter (e.g., a period of months). A recent meta-analysis of stress and HPA axis functioning found that chronically low levels of cortisol can appear after a substantial amount of time has passed since exposure to adversity (Miller, Chen, & Zhou, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…For situations that are stressful (but not traumatic; Yehuda, 2001), the body increases its production of cortisol and other glucocorticoid hormones (Friedman, 2004;Marin, Martin, Blackwell, Stetler, & Miller, 2007;Miller, Cohen, & Ritchey, 2002;Pressman et al, 2005;Segerstrom & Miller, 2004). Likewise, self-reported powerlessness predicts adrenal cortex metabolism (Samson et al, 1992), while self-affirmation prior to a challenging task buffers cortisollinked response (Creswell et al, 2005).…”
Section: Stress and Loss Of Perceived Controlmentioning
confidence: 94%